2014
DOI: 10.1039/c4sc01335b
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer interactions in self-assembled single walled carbon nanotubes/Dawson–Wells polyoxometalate hybrids

Abstract: We demonstrate the success in self-assembling pyrene-modified Dawson-Wells-type polyoxometalates (POMs) with single walled carbon nanotubes (SWCNTs) by means of p-p interactions. In this context, the immobilization of POMs onto SWCNTs is corroborated by aberration-corrected high-resolution electron microscopy, thermogravimetric analysis, and Raman spectroscopy. From steady-state and time-resolved photophysical techniques we derived evidence for mutual interactions between SWCNTs and POMs in the excited states.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 57 publications
1
34
1
Order By: Relevance
“…Instead, a mechanism of photoinduced excited‐state electron transfer from the SWNT conduction band to the LUMO of PMo 12 was more consistent . This agreed well with previous research, in which an electron‐transfer process from photoexcited SWNTs to attached POM–pyrene molecules was reported . We also found that the G band in the Raman spectra (Figure ) shifted from (1591.3±0.2) (undoped) to (1591.9±0.6) cm −1 (5 mg mL −1 PMo 12 doped) and (1592.5±0.8) cm −1 (30 mg mL −1 PMo 12 doped).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Instead, a mechanism of photoinduced excited‐state electron transfer from the SWNT conduction band to the LUMO of PMo 12 was more consistent . This agreed well with previous research, in which an electron‐transfer process from photoexcited SWNTs to attached POM–pyrene molecules was reported . We also found that the G band in the Raman spectra (Figure ) shifted from (1591.3±0.2) (undoped) to (1591.9±0.6) cm −1 (5 mg mL −1 PMo 12 doped) and (1592.5±0.8) cm −1 (30 mg mL −1 PMo 12 doped).…”
Section: Resultssupporting
confidence: 92%
“…Such spectroscopic changes were believed to result from charge transfer between doped PMo 12 and carbon nanotubes. Fluorescence loss proceeded as the doped PMo 12 concentration reached 30 mg mL −1 , but the quenching ratio was around 60 %, which was lower than that of the reported value (90 %) for a POM‐grafted SWNT hybrid . This difference lies in the direct attachment of the POM moiety to the sidewall of SWNTs in the reported case, leading to a higher efficiency in the charge transport.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…To overcome this obstacle, variousc ovalent and noncovalent linkage modes of POMs to CNTsh ave been developed. [15] These studies suggested that effective electronic connection between POMs and CNTsi sf ar from trivial and frequently hampered by the presence of bulky organic linkagesw ith restricted electron-transfer capability.T herefore, the development of efficient linkage between POMs and CNTs remains challenging. [13] Their work was extended by attaching pyrene-based organocations onto CNTst hrough p-p interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, immobilization of electroactive POMs onto graphene and carbon nanotubes has been demonstrated to show substantial advantages in terms of robustness, implementation and improved performance. 9,22,23 In the present context, POMs also provide with a heavy atom template with a well-defined structural motif, often accompanied by an recognizable symmetry, which can be easily identified by ac-TEM when deposited on carbonaceous supports. 4,9,10,13,24 In this article, we show how individual polyoxometalate anions mounted on graphene oxide (GO) supports can be imaged effectively at high voltage ac-TEM (200 kV) providing that suitably low electron doses are applied.…”
mentioning
confidence: 99%